Wanshou(万寿） Palace at Nanchang : Reproduction of the Past and Consuming history in Modern China - MIN, QI; Sikka, Sakchai (Journal of Ecohumanism, 2024)
This paper discusses the past reproduction and consuming historical phenomenon of Wanshou(万寿） Palace historical and cultural Block in Nanchang under the background of modern China. Wanshou(万寿）Palace, bearing a historical precipitation of more than 1700 years, is a symbolic cultural landscape of Nanchang. Its restoration and block protection are not only the material reproduction of buildings and blocks, but also the continuation of the cultural and spiritual aspects of Wanshou(万寿） Palace. The research uses the qualitative analysis method to deeply analyze the development process of the Tiezhu Wanshou（铁柱万寿） Palace, the architectural art characteristics and the concept and practice of modern China heritage protection. It is found that the Wanshou(万寿） Palace historical and cultural block, through the mutual support and cooperation of the Nanchang municipal government, scholars and the community, has profound practical significance for the reproduction of the past history and consuming history. Effectively combine Wanshou(万寿） Palace culture with modern consumption to provide an immersive cultural experience for citizens and tourists. However, the behavior of consuming history in the process of cultural heritage protection has a two-sided nature. People need to pay attention to the authenticity of culture in the process of protecting historical heritage and inheriting cultural value. This study provides practical planning suggestions and impact assessment for the historical and cultural construction and the sustainable development mode of cultural tourism in Nanchang, and provides valuable classics for the protection of historical heritage and the integration of historical reproduction and modern consumption in other cities.